Waterborne Pathogens Detection and Treatment - Vara Prasad, Majeti Narasimha; Vara Prasad, Majeti Narasimha; Grobelak, Anna (Butterworth-Heinemann, 2020)
Waterborne Pathogens: Detection and Treatment delivers the tools and techniques on how to identify these contaminates and apply the most effective technology for their removal and treatment. Written for researchers and practicing professionals, the book starts with a brief, but readable, review of ubiquitous waterborne pathogens (primarily viruses, bacterial and parasitic protozoa). This coverage is followed by an in-depth discussion of the latest detection and treatment technologies, ranging from Biosensors, to Nanoconjugates, Membrane Based Technologies and Nanotechnology Treatment. Engineers and scientist will find this to be a valuable reference on cutting-edge techniques for suppling safe drinking water across the globe. - Explains the latest research on detection, treatment processes and remediation technologies - Includes sampling, analytical and characterization methods and approaches - Covers cutting-edge research, including Membrane Based Technologies, Nanotechnology Treatment Technologies and Bioremediation Treatment Technologies - Provides background information regarding contamination sources